2012
DOI: 10.1007/s11136-012-0334-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a new quality of life scale related to multiple sclerosis and relapses

Abstract: The PERSEPP scale has been validated and could be used in clinical trials and in daily practice. Additional studies will then complete the validation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…A better understanding of a chronic disease requires a comprehensive approach to take different components into account, especially when it comes to the quality of life as a multi-dimensional aspect (27). A previous attempt to develop measures related to the quality of life in MS resulted in the PERSEPP scale ("PERception de la Sclérose En Plaques et de ses Poussées") (28). Five dimensions of that scale target social support, relationship difficulties, fatigue, state of mind and associated sleep disorders, and time perspective.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of a chronic disease requires a comprehensive approach to take different components into account, especially when it comes to the quality of life as a multi-dimensional aspect (27). A previous attempt to develop measures related to the quality of life in MS resulted in the PERSEPP scale ("PERception de la Sclérose En Plaques et de ses Poussées") (28). Five dimensions of that scale target social support, relationship difficulties, fatigue, state of mind and associated sleep disorders, and time perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Total score of PERCEPP questionnaire was significantly correlated with SF36 and QoL54 questionnaires that could show convergent validity that is consistent with Baroin et al ., study. [ 17 ] In their study, symptoms and treatment subscales were significantly different between cases with different EDSS scores while in this study, mean relationship difficulties and coping were significantly different. This could be indicative of impact of advanced disease on managing the personal and inter personal relations.…”
Section: Discussionmentioning
confidence: 46%
“…Their results also showed that ICC score of all items was above 0.7, which are consistent with our results. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that relapse may have a negative impact on patients' QoL, we developed a scale named PERSEPP ("PERception de la Sclérose En Plaques et de ses Poussées") in order to assess the impact of MS relapses and the disease in everyday life of patients in terms of QoL (Baroin et al, 2010). Indeed, it seems necessary to evaluate this difficult period in patients' lives.…”
Section: Several Scales Have Already Been Validated In the Field Of Mmentioning
confidence: 99%